Author Correction: Kawasaki Disease following administration of 13-valent pneumococcal conjugate vaccine in young children (Scientific Reports, (2019), 9, 1, (14705), 10.1038/s41598-019-51137-5) - Yung, Chee Fu (Nature Research, 2022)
10.1038/s41598-021-87465-8